Antimicrobial Resistance and Molecular Epidemiology of Escherichia coli From Bloodstream Infection in Shanghai, China, 2016–2019 - Xiao, Shuzhen; Tang, Chenyue; Zeng, Qian; Xue, Yilun; Chen, Qing; Chen, Erzhen; Han, Lizhong (Frontiers in Medicine, 2022)
Background: Bloodstream infections (BSIs) are recognized as important nosocomial infections. Escherichia coli (E. coli) is the most prevalent Gram-negative bacillary pathogen causing BSI. This retrospective study investigated drug susceptibility and molecular epidemiology of E. coli isolated from patients with BSI in Shanghai, China. Methods: We collected E. coli isolated from blood cultures of patients with BSI between January 2016 and December 2019. We randomly selected 20 strains each year to investigate antimicrobial resistance, resistance genes and molecular epidemiological characteristics. Antimicrobial susceptibility testing was performed by disk diffusion method. PCR was performed to detect extended-spectrum β-lactamases (ESBLs), carbapenemase genes and housekeeping genes, and phyloviz was applied to analyze multilocus sequence typing (MLST). Results：Penicillins, first and second- generation cephalosporins and fluoroquinolones have high resistance rates (>60%). Of the 80 randomly selected strains, 47 (58.8%) produced ESBLs and one produced carbapenemase. Sequencing of resistance genes identified blaCTX-M-14 (34%, 16/47), blaCTX-M-15 (23.4%, 11/47) and blaCTX-M-27 (14.8%, 7/47) as the most prevalent genotypes of ESBLs. ST131 (14/80) was the most prevalent sequence type (ST), followed by ST1193 (10/80), ST648 (7/80). Conclusions: Our findings suggest that amikacin, carbapenems, and piperacillin-tazobactam have relatively low resistance rates and may be the preferred antibiotic regimens for empiric therapy. ST131 and blaCTX-M-14 are still the main prevalent in Shanghai with a rapid increase in the occurrence of ST1193 is rapidly increasing and more diverse blaCTX genes.